Hypothalamic glucose sensing: making ends meet - Routh, Vanessa H.; Hao, Lihong; Santiago, Ammy M.; Sheng, Zhenyu; Zhou, Chunxue (Frontiers in Systems Neuroscience, 2014)
The neuroendocrine system governs essential survival and homeostatic functions. For example, growth is needed for development. Thermoregulation maintains optimal core temperature in a changing environment. Reproduction ensures species survival. Stress and immune responses enable an organism to overcome external and internal threats. The circadian system regulates arousal and sleep such that vegetative and active functions do not overlap. All of these functions require a significant portion of the body’s energy. As the integrator of the neuroendocrine system, the hypothalamus carefully assesses the energy status of the body in order to appropriately partition resources to provide for each system without compromising the others. While doing so the hypothalamus must ensure that adequate glucose levels are preserved for brain function since glucose is the primary fuel of the brain. To this end, the hypothalamus contains specialized glucose sensing neurons which are scattered throughout the nuclei controlling distinct neuroendocrine functions. We hypothesize that these neurons play a key role in enabling the hypothalamus to partition energy to meet these peripheral survival needs without endangering the brain’s glucose supply. The goal of this review is to describe the varied mechanisms underlying glucose sensing in neurons within discrete hypothalamic nuclei. We will then evaluate the way in which peripheral energy status regulates glucose sensitivity. For example, during energy deficit such as fasting specific hypothalamic glucose sensing neurons become sensitized to decreased glucose. This increases the gain of the information relay when glucose availability is a greater concern for the brain. Finally, changes in glucose sensitivity under pathological conditions (e.g., recurrent insulin-hypoglycemia, diabetes) will be addressed. The overall goal of this review is to place glucose sensing neurons within the context of hypothalamic control of neuroendocrine function.